Does customer satisfaction impact linearly on loyalty and retention levels? - Vasconcelos, Inês Filipa Ambrósio (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Information Analysis and Management